2013
DOI: 10.5056/jnm.2013.19.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors for Response to Proton Pump Inhibitor Treatment in Patients With Globus

Abstract: Background/AimsGlobus is a persistent or intermittent non-painful sensation of a lump or foreign body in the throat. Given the benign nature of the condition and the association of gastroesophageal reflux disease, empirical therapy with proton pump inhibitor seems reasonable for patients with typical globus. The aim of this study was to investigate the clinical predictors for symptom response to short-term proton pump inhibitor treatment in patients with globus symptom.MethodsFifty-four patients with globus sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Our results suggested that the more acid reflux is involved in the etiology of patients with globus sensation, the more effective PPI becomes even though the duration of administration of PPI is relatively short. A recent study by Jeon et al also showed the same results as ours, namely that the presence of reflux symptoms and short symptom duration were independent predictors of responsiveness to 4-week PPI treatment in patients with globus sensation (53). …”
Section: Treatmentsupporting
confidence: 85%
“…Our results suggested that the more acid reflux is involved in the etiology of patients with globus sensation, the more effective PPI becomes even though the duration of administration of PPI is relatively short. A recent study by Jeon et al also showed the same results as ours, namely that the presence of reflux symptoms and short symptom duration were independent predictors of responsiveness to 4-week PPI treatment in patients with globus sensation (53). …”
Section: Treatmentsupporting
confidence: 85%
“…All other patients were defined as non-responders. 50% or more decrease was chosen based on the value used in previous studies that examined drug effects on globus sensation [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Improvement ratio of somatic distress showed significant correlation with that of the GETS-J pain/swelling subscale There were 14 responders and 17 non-responders, indicating that the overall effective rate of the P-CAB treatment on AST was 45.1%. Pantoprazole (40 mg), one of the PPIs, for four weeks showed an effective rate of 35.7% [19] and 53.7% [20] when the same threshold to determine the responders (> 50% reduction in symptom scores) was used. Our results of P-CAB (45.1%) were comparable with these studies.…”
mentioning
confidence: 99%
“…PPI was primarily considered to be the first‐line treatment of globus given that GERD had been suggested to be a major cause. Unfortunately, prior studies using PPI yielded inconsistent outcomes 7,8 . There were a few of trials which proved the benefit of low‐dose tricyclic antidepressants (TCA) such as amitriptyline or selective serotonin reuptake inhibitor (SSRI) such as paroxetine 9–11 .…”
Section: Introductionmentioning
confidence: 99%